(untitled) (Physical Education, Health and Social Sciences, 2025)
In the digital era of self-presentation, Instagram platforms among other platforms has become an emergent and dominant in shaping the body perceptions in youth. This study investigates the relationship between Instagram use, muscle dysmorphia (MD), and psychological distress in late adolescents (15–17 years) and young adult males (18–25 years). Employing a comparative cross-sectional design, 150 male gym-goers who reported active Instagram use were recruited through purposive sampling. The Appearance-Related Social Media Consciousness Scale (adapted for Instagram), the Drive for Muscularity Scale, and the Kessler Psychological Distress Scale were used to gather data. Results revealed strong positive correlations between Instagram use and MD (r = .70, p < .01), Instagram use and psychological distress (r = .55, p < .01), and MD and psychological distress (r = .60, p < .01). Regression analyses further confirmed that MD significantly mediated the relationship between Instagram use and psychological distress, with Instagram use predicting 49% of the variance in MD, and MD partially accounting for the variance in distress levels (ΔR² = .14). These findings highlight the psychological risks associated with high appearance-focused engagement on Instagram, especially in developmental stages marked by heightened body image vulnerability. The study underscores the need for preventive strategies and digital literacy programs to address body dissatisfaction and emotional distress linked to social media exposure. Interventions targeting appearance comparison and unrealistic muscular ideals are crucial in fostering healthier social media use and promoting psychological well-being among adolescent and young adult males.